EFFECT OF USING GINGER AND TUMERIC FOR MARINATION ON THE MICROBIAL COUNT OF SPENT LAYERS MEAT - Kaboshio, K. Y.; Gandi, B. R.; Aliyu, Z. I.; Bature, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluates the effect of using ginger and turmeric for marination on the microbial count of spent layer meat. Sixteen (16) spent layers were used for the study and a total of four treatments: grilled control (no marination), grilled with ginger, grilled with turmeric, grilled with ginger and turmeric, fresh control (no marination), fresh with ginger, fresh with turmeric, fresh with ginger and turmeric, and four replications having one (1) spent layer in each replicate, were used for the study. Findings from the study showed that, meat without marination had a high microbial load, indicating vulnerability to spoilage and contamination. Ginger treatment reduced TBC to 1.50E+07 CFU/g, demonstrating its antimicrobial properties. Turmeric treatment recorded the highest TBC at 2.67E+07 CFU/g. This suggests that the addition of turmeric may create a condition for certain bacteria to thrive. The combination treatment yielded a total bacterial count (TBC) of 1.19E+07 CFU/g, suggesting a synergistic effect. The findings for total fungal count (TFC) showed significant differences (P<0.05), with ginger's efficacy against bacteria being limited. The combination treatment of turmeric and ginger showed the highest TFC at 2.30E+06 CFU/g. This suggests that the combination of turmeric and ginger as marinade may not effectively control fungal growth and could promote spoilage. The study recommends the combination of ginger and turmeric for marination due to their antimicrobial properties.